Isolation and Crystallographic Characterization of the Labile Isomer of Y@C82 Cocrystallized with Ni(OEP): Unprecedented Dimerization of Pristine Metallofullerenes. (15th June 2016) - Bao, Lipiao; Pan, Changwang; Slanina, Zdenek; Uhlik, Filip; Akasaka, Takeshi; Lu, Xing
Abstract: Although the major isomers of M@C82 (namely M@ C 2 v (9)‐C82, where M is a trivalent rare‐earth metal) have been intensively investigated, the lability of the minor isomers has meant that they have been little studied. Herein, the first isolation and crystallographic characterization of the minor Y@C82 isomer, unambiguously assigned as Y@ Cs (6)‐C82 by cocrystallization with Ni(octaethylporphyrin), is reported. Unexpectedly, a regioselective dimerization is observed in the crystalline state of Y@ Cs (6)‐C82 . In sharp contrast, no dimerization occurs for the major isomer Y@ C 2 v (9)‐C82 under the same conditions, indicating a cage‐symmetry‐induced dimerization process. Further experimental and theoretical results disclose that the regioselective dimer formation is a consequence of the localization of high spin density on a special cage‐carbon atom of Y@ Cs (6)‐C82 which is caused by the steady displacement of the Y atom inside the Cs (6)‐C82 cage.